2019
DOI: 10.2478/s11686-019-00151-8
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Molecular Characteristics of the Gastro-Intestinal Nematode Parasite Ascaridia columbae Infecting the Domestic Pigeon Columba livia domestica in Saudi Arabia

Abstract: Background Parasitism is a complex problem that is often ignored in companion animals, including birds, unless it develops into a severe clinical disorder. The present study was, therefore, aimed to investigate the presence of the gastrointestinal nematode infecting the domestic pigeon and provide a complete morphological description and clarify its taxonomic position through phylogenetic analysis of the ITS1-5.8s-ITS2 rDNA gene region. Materials and MethodsDuring the current study, a total of twenty-six domes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 78 publications
(88 reference statements)
4
11
0
Order By: Relevance
“…The identification of A. columbae depends on ultramicroscopic identification of the nematode and analysis of the ITS gene; this study reveals that the morphological identification confirmed the infection of examined pigeon with A. columbae nematod. In this study; the morphological identification was similar to a previous study recorded by Al Quraishy et al. 2020 ; which studied the A. columbae by SEM, which based upon different characteristic features that confirm the recovered nematod is A. columbae ; these features are (well-developed lips; a cuticular organization with the presence of transverse annuli; pre-cloacal sucker the number and distribution of the cloacal papillae; a vulva near the middle region of the body) this study similar as Khalil et al.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The identification of A. columbae depends on ultramicroscopic identification of the nematode and analysis of the ITS gene; this study reveals that the morphological identification confirmed the infection of examined pigeon with A. columbae nematod. In this study; the morphological identification was similar to a previous study recorded by Al Quraishy et al. 2020 ; which studied the A. columbae by SEM, which based upon different characteristic features that confirm the recovered nematod is A. columbae ; these features are (well-developed lips; a cuticular organization with the presence of transverse annuli; pre-cloacal sucker the number and distribution of the cloacal papillae; a vulva near the middle region of the body) this study similar as Khalil et al.…”
Section: Discussionsupporting
confidence: 90%
“…Our study in molecular characterization used the PCR sequencing of the (ITS1-5.8sITS2) of the rDNA gene region, which confirmed that the collected Ascidida belongs to A. columbae nematod. A similar study was recorded by Al Quraishy et al. 2020 (A. columbae) and Gomes et al.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…It is also possible that domestic pigeons may serve as alternative hosts for some poultry helminths with which they interact and are closely related phylogenetically (Michel, 1974). Helminths that are localized in the intestines of birds significantly affect the functional activity of the immune system, cause immunodeficiency, reduce the natural reactivity of the infected organism (Biswal et al, 2016;Al Quraishy et al, 2020).…”
Section: Introductionmentioning
confidence: 99%